Penanaman Bibit Tanaman Sayur Dengan Media Polybag Untuk Mendukung Ketahanan Pangan Masyarakat Desa Tumenggungan - Chairani Astina; Muhammad Galang Aji Saputra; Koniu Aliza; Nur Muhamad Kadafi; Faiq Yuhri; Ayu Puji Rakhmawati; Puput Fitrianingsih (Jurnal Pengabdian Masyarakat Madani, 2022)
In the world of agriculture and plantations, we often hear the term polybag as a planting medium, especially in nurseries and planting in polybags to save agricultural land. The selection of polybags as planting containers for cultivation is influenced by several factors, such as low prices, rust resistance, durability, light weight, uniform shape, not getting dirty quickly and easy to obtain at agricultural supply stores or plastic stores. In addition, polybags are very good for drainage, aeration so that plants can thrive like in the field. Determining the size of polybags that are suitable for plant growth is expected to increase productivity and efficiency in the use of media and nutrients. On the other hand, the cultivation of healthy and fresh organic vegetables has a positive impact on the surrounding environment which is increasingly beautiful and healthy. This Community Service activity involved KWT women in the Tumenggungan area, including women from RT07 Dusun Karangtengah. The women of KWT RT07 Dusun Karangtengah will later gain practical knowledge about organic vegetable cultivation that can be applied in the future.